Visualizing Commognitive Responsibility Shift in Collaborative Problem-Solving During Computer-Supported One-to-One Math Tutoring - Lu, Jijian; Tuo, Pan; Feng, Ruisi; Stephens, Max; Zhang, Mohan; Shen, Zhonghua (Frontiers in Psychology, 2022)
This study aims to use a commognitive responsibility framework to visualize responsibility shift in collaborative problem-solving during computer-supported one-to-one tutoring. Commognitive responsibility shift means that individuals’ cognitive responsibility shift can be reflected by the discourse in communication. For our sample we chose a 15-year-old Chinese boy and his mathematics teacher with 6 years’ experience, both of whom have experienced computer-supported teaching and learning of mathematics. We collected four tutoring videos (each 60-90 minutes, in total more than 330 minutes) online, and 45 minutes interview video from the teacher. We found that the third type of commognitive responsibility shift in both the teacher's and student’s collaborative problem solving behavior online is not only teacher-student comparison but also alternating-led, which includes teacher-student-led and student-teacher-led.